The Influence of Attribution Style and Goal Accessibility on Health Beliefs and Exercise Willingness: Experimental Evidence from University Students - Shuai Zhang; Chenglong Miao (Behavioral Sciences)
Although the benefits of regular physical activity are widely recognized, many university students fail to sustain consistent exercise behaviors. This phenomenon may be attributed to cognitive and motivational barriers, particularly perceptions of goal attainability and attribution styles, which are believed to significantly influence students’ health beliefs and intentions to engage in physical activity. This research aimed to examine the independent and combined effects of goal attainability and attribution style on Chinese university students’ health beliefs and willingness to exercise. The study also investigated how shifts in attribution style may influence these outcomes under different levels of goal attainability. Two between-subjects experiments were conducted. In Experiment 1 (N = 146), a 2 (goal attainability: high vs. low) × 2 (attribution style: internal vs. external) design was used. Participants were exposed to tailored exercise advertisements and completed standardized questionnaires measuring health beliefs and exercise intentions. Experiment 2 (N = 130) adopted a 2 (goal attainability: high vs. low) × 2 (attributional shift: external-to-internal vs. internal-to-external) design, utilizing visual priming and short video interventions to manipulate attributional orientation. In Experiment 1, both high goal attainability and internal attribution independently enhanced participants’ health beliefs and exercise willingness. A significant interaction effect was observed only for exercise willingness, with the highest intentions found in the high attainability × internal attribution group. In Experiment 2, shifting attribution from external to internal significantly increased both health beliefs and exercise willingness, while shifting from internal to external resulted in substantial decreases. An interaction effect was again found only for exercise willingness, suggesting that the effectiveness of attributional shift depended on goal attainability. By integrating the Health Belief Model with Attribution Theory, this study offers a deeper understanding of how cognitive and motivational factors influence exercise behavior, and provides a theoretical foundation for developing adaptive interventions.